Developing Module for Entrepreneurship Based Translation and Interpreting Skills Course in English Language Teacher Education - Siyaswati, Siyaswati; Rochmawati, Dyah (Universitas PGRI Adi Buana Surabaya, 2019)
The present study describes the development of a course module on Entrepreneurship-Based Translation and Interpretation Skills for the students of English Language Teacher Education Department. The module was inspired by empirical research findings about the knowledge base of student teachers. It was created and refined during its three-year application will be reflected upon here, including feedback collected from student evaluation sheets. In the end, the participants responded positively to the course module. The students stated that the module was interesting, relevant and valuable for their later profession. They also emphasized that they now felt more competent in the area of Translation and Interpretation Skills and entrepreneurship.